THE ROLE OF EMERGENCY PSYCHIATRY SOCIAL WORK IN A VIRTUAL CLINIC DURING THE COVID-19 PANDEMIC - Stepho, Ethan; Heinrich-Williams, Marta; Dunne, Lori; Raymond, Holly; Parthasarathi, Usha (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2020)
The Psychiatry Emergency Services (PES) virtual clinic is an innovative clinical program that was established to enhance access to psychiatric crisis follow-up care during COVID-19. The clinic provides psychiatric follow-up via scheduled phone calls or videoconference for patients that have been seen by the PES team. The social worker has an important role on the PES virtual clinic team: they initiate initial assessments, collaboratively develop follow-up plans, and facilitate community care. The clinic meets the provincial agenda to reduce Emergency Department (ED) visits, ED/PES wait times, ED/PES overcrowding, and inappropriate admissions, while addressing both psychiatric needs and social determinants of health in an acute care setting. Throughout our survey of relevant literature, we found little research to inform the implementation of virtual care in Canadian healthcare emergency services (Hensel et al., 2020; Serhal et al., 2017). More specifically, there is a void in research regarding a collaborative psychiatric and social work care model in the context of a global pandemic. Further robust studies are needed and encouraged that use emergency psychiatric settings as critical prevention sites of mental health crises.